(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This piece explores the comparative aspects of the two folk heroic epics from Uzbekistan and England and particularly contrasts their thematic, structural, and linguistic features. While relying on Alpomish and Beowulf to provide prototypes, the exposition probes into the extent to which these two giants of oral tradition embody the moral virtues, social hierarchy, and spiritual convictions of their respective cultural milieus. It dwells on the role of performance art as the primary vehicle of the collective memory and the main mode of transmitting the national ethos from one generation to another. Besides, the two epics devote very similar accounts of the hero as the epitome of valor, loyalty, and moral uprightness; therefore, they convey the message of the importance of courage and honor as instruments of social peace. Although they differ in terms of historical background and worldview—Alpomish as nomadic-patriarchal and Beowulf as warrior-Christian narrative—both works teem with universal human themes of heroism, self-sacrifice, and eternal conflict between the forces of good and evil. Their authorship is thus seen as two-sided artistic reflections that, acting as mirrors, both preserve the historical and ethical identity of their peoples.